Pengaruh Gaya Kepemimpinan terhadap Komitmen Organisasional (Sistem Pengendalian Manajemen sebagai Variabel Moderasi) - Izza Ashsifa (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2020)
The purpose of this study is to fill the gap in the management accounting literature by integrating the role of management control systems on leadership style and organizational commitment. Data collection techniques in this study used an online survey by distributing the questionnaires to management accountants throughout Indonesia. SEM-PLS was used to test the hypothesis with a sample size of 158. The results showed that elements of formal and informal control systems, such as outcomes, actions, personnel and culture, influenced leadership behavior and the development of organizational commitment.Keywords: management control system, leadership style, initiation structure, consideration, organizational commitment.